Growth/differentiation factor-15 inhibits differentiation into osteoclasts--a novel factor involved in control of osteoclast differentiation - Vanhara, Petr; Lincová, Eva; Kozubík, Alois; Jurdic, Pierre; Soucek, Karel; Smarda, Jan (Differentiation; research in biological diversity, 2009)
Survival and capability of cancer cells to form metastases fundamentally depend on interactions with their microenvironment. Secondary tumors originating from prostate carcinomas affect remodeling of bone tissue and can induce both osteolytic and osteocondensing lesions. However, particular molecular mechanisms responsible for selective homing and activity of cancer cells in bone microenvironment have not been clarified yet. Growth/differentiation factor-15 (GDF-15), a distant member of the TGF-beta protein family, has recently been associated with many human cancers, including prostate. We show that both pure GDF-15 and the GDF-15-containing growth medium of 1,25(OH)(2)-vitamin D(3)-treated prostate adenocarcinoma LNCaP cells suppress formation of mature osteoclasts differentiated from RAW264.7 macrophages and bone-marrow precursors by M-CSF/RANKL in a dose-dependent manner. GDF-15 inhibits expression of c-Fos and activity of NFkappaB by delayed degradation of IkappaB. Moreover, GDF-15 inhibits expression of carbonic anhydrase II and cathepsin K, key osteoclast enzymes, and induces changes in SMAD and p38 signaling. The lack of functional osteoclasts can contribute to accumulation of bone matrix by reduction of bone resorption. These results unveil new role of GDF-15 in modulation of osteoclast differentiation and possibly in therapy of bone metastases.
Keywords: buněčná diferenciace; Male; Time Factors; makrofágy; Osteoclasts; Prostatic Neoplasms; Dose-Response Relationship, Drug; NF-kappa B; Animals; Proto-Oncogene Proteins c-fos; časové faktory; vztah mezi dávkou a účinkem léčiva; Humans; Mice; femur; karboanhydrasa II; inbrední kmeny myší; kyselá fosfatasa rezistentní k tartarátu; Acid Phosphatase; mužské pohlaví; Macrophage Colony-Stimulating Factor; Macrophages; Tartrate-Resistant Acid Phosphatase; ligand RANK; RANK Ligand; Femur; Cathepsin K; kathepsin K; Mice, Inbred Strains; osteoklasty; Growth Differentiation Factor 15; Calcitriol; faktor stimulující kolonie makrofágů; Cell Line; Cell Line, Tumor; Cell Differentiation; nádorové buněčné linie; zvířata; kyselá fosfatasa; nádory prostaty; Isoenzymes; izoenzymy; Culture Media, Conditioned; Carbonic Anhydrase II; lidé; kultivační média speciální; protoonkogenní proteiny c-fos; růstový diferenciační faktor 15; buněčné linie; kalcitriol; myši